The Relationship Between Active Case Finding Of Rheumatic Heart Disease Through Echocardiographic Screening And Nutritional Status In Children Aged 5 – 15 Years Old In Surabaya, Indonesia - Laksitarini, Asri; Lefi, Achmad; Yusuf Alsagaff, Mochamad (Journal of Neonatal Surgery, 2025)
Rheumatic heart disease (RHD) is a sequel of acute rheumatic fever (ARF) caused by an autoimmune reaction to group A beta-hemolytic streptococcal (GAS) infection. Although RHD is a preventable disease, it remains a significant health issue, particularly in developing countries like Indonesia, which has the fourth highest prevalence globally with 1.18 million cases each year. Diagnosing ARF and RHD in tropical regions poses challenges, compounded by the limited number of trained screening operators capable of performing and interpreting echocardiograms. The highest incidence of ARF occurs in children aged 5 to 15 years, making this age group a primary target for secondary antibiotic prophylaxis to reduce recurrence and the progression of RHD. This study is expected to serve as an initial step in prophylactic strategies to hinder the development of RHD, improve early therapeutic management, and support Sustainable Development Goals (SDG) indicators in achieving good health and community well-being. This study is a cross-sectional research. The subjects of the study are school-aged children (5-15 years) from schools scattered throughout Surabaya. Data collection includes basic characteristic data and echocardiographic examinations conducted by trained general practitioners using portable transthoracic echocardiography. Screening is categorized into positive and negative screening according to the World Heart Federation guidelines 2023. A total of 403 children aged 5 to 15 years participated in the study, with 71.2% classified as negative and 28.8% as positive for rheumatic heart disease (RHD) based on screening. Younger children in elementary school had a significantly higher prevalence of positive screening results (36.4%) compared to junior high school students (18.6%, p < 0.001). Based on the Spearman test results, a p-value of 0.900 was obtained, which is > 0.05, indicating that there is no significant relationship between rheumatic heart disease screening and nutritional status.